PHYSICAL, STATO-KINETIC DEVELOPMENT AND MORBIDITY OF CHILDREN WITH BRONCHOPUL-MONARY DYSPLASIA WITHIN TWO YEARS OF THEIR LIFE - Oskomenko, M.M.; Chernyavska, Y.I.; Kovaleva, O.M.; Tsvirenko, S.M.; Pohylko, V.I. (World of Medicine and Biology, 2016)
The article is devoted to dynamic analysis investigation of individual growth components of children with bronchopulmonary dysplasia, studying the frequency of acute infectious respiratory diseases, anemia, rickets, food allergies within two years of their life. It was the cohort prospective study that included 33 children with bronchopulmonary dysplasia. In all children, which were under 24 months of age and were observed in the center of the child, stato-kinetic, psycho-emotional, speech development and incidence of acute infectious respiratory disease in 6, 12, 18 and 24 months of chronological and adjusted age were evaluated. The results of this study showed that children with bronchopulmonary dysplasia, that were discharged from medical institutions, in assessing the WHO scales of physical development, almost in 50 % had delayed physical development, at the age of two years, 36,9 % of infants had weight below 10 %; 41,7 % of children had a height lower than 10 %; 41,7 % of infants had chest circumference below 10 % and 33,3 % of head circumference below 10 %. 48 % of children had anemia at discharge from the hospital, and at six months of age – 52,0 %. At 12 and 18 months of age the number of children who had anemia decreased significantly to 13,6 % (p=0,005).